2019
DOI: 10.1590/1807-3107bor-2019.vol33.0050
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of bisphosphonate-related osteonecrosis using platelet-rich plasma: microtomographic, microscopic, and immunohistochemical analyses

Abstract: Camila Lopes CARDOSO (a) Cláudia CURRA (a) Marcos Martins CURI (b) Mariza Akemi MATSUMOTO (c) Camila Dionísio ARGENTINO (a) Solange de Oliveira Braga FRANZOLIN (d) Dulce CONSTANTINO (d) Daniela Nicolielo BARBOSA (d) Osny FERREIRA JÚNIOR (e)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…FBS, fetal bovine serum; tPRP, thrombin-activated platelet-rich plasma [Colour figure can be viewed at wileyonlinelibrary.com] driven by a higher density of osteoprogenitors in the constructs. A superiority of PRP over FBS in terms of bone formation in an osteonecrosis model was already reported elsewhere also, but only when applied directly, that is, without cells and compared with no treatment (Cardoso et al, 2019). It has also been shown that culture of adipose-derived stromal cells with PRP increased not only their proliferation capacity but also the direct osteogenic differentiation of the progenitor cells present in the SVF (Hong et al, 2019).…”
Section: Bone Formationsupporting
confidence: 58%
“…FBS, fetal bovine serum; tPRP, thrombin-activated platelet-rich plasma [Colour figure can be viewed at wileyonlinelibrary.com] driven by a higher density of osteoprogenitors in the constructs. A superiority of PRP over FBS in terms of bone formation in an osteonecrosis model was already reported elsewhere also, but only when applied directly, that is, without cells and compared with no treatment (Cardoso et al, 2019). It has also been shown that culture of adipose-derived stromal cells with PRP increased not only their proliferation capacity but also the direct osteogenic differentiation of the progenitor cells present in the SVF (Hong et al, 2019).…”
Section: Bone Formationsupporting
confidence: 58%
“… 13 To effectively prevent patients from BRONJ after tooth extraction, clinical operations such as early wound closure after tooth extraction, hyperbaric oxygen therapy, stem cell therapy, and growth factor are mostly used, but there are few clinical data and it is difficult to reach a consensus. 14 17 Therefore, at this stage, the clinic advocates prevention for BRONJ.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have focused on the regenerative potentialities and translational applications of PRP ( Cardoso et al., 2019 ; Inchingolo et al., 2017 ) associated with the choice of the best scaffold seeded with different SCs such as dental-derived SCs ( Ballini et al., 2017 ), mesenchymal SCs ( Cantore et al., 2018 ), and adipose-derived SCs ( Barba-Recreo et al., 2015 ) in the regenerative medicine such as the management of medication-related osteonecrosis of the jaw ( Boccaccio et al., 2018 ; Crincoli et al., 2015 ). Since the pathogenesis of BRONJ as well as its prevention and treatment has not been established, this study was aimed to investigate the success of applying PRP + collagen scaffold and collagen scaffold alone in prevention of zoledronic acid-induced BRONJ grossly, histologically, and radiographically in the rat animal model.…”
Section: Discussionmentioning
confidence: 99%